INOVASI BAHAN AJAR PAI BERBENTUK MODUL - Jalaluddin (Journal of Contemporary Indonesian Islam, 2025)
The dynamic nature of education requires innovative teaching materials that meet 21st-century learning demands, including in Islamic Religious Education (PAI). This study aims to develop an innovative, contextual, and student-centered PAI module to enhance learning effectiveness and independence. The research employed a Research and Development (R&D) design using the ADDIE model, covering needs analysis, product design, module development, classroom implementation, and evaluation. Participants included grade X students at a public senior high school in North Aceh, as well as expert validators in content, instructional design, and educational practice. Results show that the module achieved high validation scores in terms of content quality, language, and presentation. Limited classroom trials revealed significant improvement in student learning outcomes and positive responses regarding usability, design appeal, and relevance. The study concludes that such modules enrich learning resources, support individual needs, and recommends integrating technology and project-based learning to further strengthen PAI instruction.